Charles-Ferdinand Ramuz, i Copiaus e le creazioni collettive: prove di drammaturgia - Carponi, Cecilia (Mimesis Journal, 2018)
La Guerre des filles et des garçons, found in the Fond Michel Saint-Denis, is an unpublished scenario drafted in 1928 by the Swiss author Charles-Ferdinand Ramuz, Jean Villard-Gilles and Michel Saint-Denis for the Copiaus. This «vague projet», which was never carried out nor performed, gets interesting especially if compared with the earlier collective creations produced in Burgundy by Jacques Copeau’s disciples. For the first time, indeed, the Copiaus’ purely scenic language is looking for a solid dramaturgical frame, unlike La Danse de la Ville et des Champs and Les Jeunes gens et l’araignée ou La Tragédie imaginaire, where acting led the creative process. The Compagnie des Quinze, founded in the earlier 1930s in Paris by Saint-Denis and some ex Copiaus, will apply and develop this formula with the collaboration of the author André Obey, with a view to opening towards a theatre synthesis between performing language and dramaturgical structure. This process results for elective descent from the Commedia dell’Arte and is essential to understand the shift from the classical figure of the author to the one of the dramaturg.